Perancangan Ulang Interior Le Dian Hotel & Cottages Di Kota Serang Dengan Pendekatan Aktivitas Bisnis - Nafis Khalaid, Nadiva; Firmansyah, Rangga; Sri Ismiranti, Athifa (eProceedings of Art & Design, 2024)
Le Dian Hotel & Cottages, a 4-star business hotel in Serang City, faces challenges in accommodating the needs of guests' business activities. This design aims to redesign the hotel interior with the approach of "Dynamic Business Hub: Fusing Modernity with Local Inspiration" to create a productive and comfortable environment. The methods used include the creation of a warm and calm interior atmosphere, functional layout, modern visuals with a touch of Banten cultural locality, as well as the fulfillment of optimal general space requirements. Thus, the interior becomes more organized, functional, and aesthetic, with clear division of areas, efficient furniture layout, and optimal lighting and ventilation. This redesign creates an environment that supports the productivity and comfort of business guests, and gives the hotel a unique identity and is beneficial to the hospitality industry in understanding the importance of design that focuses on business activities and combines modernity with local wisdom. Keywords: design, business hotel, business activity, modernity